VD_FINDINFO Jug / 2018 / 268 vom 22. Januar 2018 - VD Tribunal cantonal (2018)
MEURTRE, ASSASSINAT, FIXATION DE LA PEINE, CONSTATATION DES FAITS, TORT MORAL | 47 CO, 111 CP, 112 CP, 47 CP, 10 CPP (CH), 398 al. 3 let. b CPP (CH), 433 CPP (CH)